Combining an optimized mRNA template with a double purification process allows strong expression of in vitro transcribed mRNA - Sergio Linares-Fernández; Julien Moreno; Elise Lambert; Perrine Mercier-Gouy; Laetitia Vachez; Bernard Verrier; Jean-Yves Exposito (Elsevier, 2021)
mRNA is a blooming technology for vaccination and has gained global attention during the SARS-CoV-2 pandemic. However, the recent clinical trials have highlighted increased reactogenicity when using high mRNA doses. Intending to increase the potency of mRNA therapeutics and to decrease the therapeutic dose, we designed a mRNA backbone and optimized the mRNA purification process. We used the enhanced green fluorescent protein (eGFP) reporter gene flanked by one 5' untranslated region (UTR) and two 3' UTRs of the human β-globin as a reference mRNA and identified the most promising mRNA sequence using in vitro and in vivo models. First, we assessed the impact of different poly(A) sizes on translation and selected the most optimal sequence. Then, we selected the best 5' UTR among synthetic sequences displaying a high ribosome loading. Finally, we evaluated the transfection efficiency of our standard mRNA template after two capping strategies and purification using either double-stranded RNA (dsRNA) depletion or dephosphorylation of 5'PPP RNA or both combined. Double purification was shown to give the best results. Altogether, the use of a newly defined 5' UTR coupled to post-transcriptional treatments will be of great interest in the mRNA vaccine field, by limiting the amount of the antigen-coding transcript and subsequently the formulation components needed for an efficient vaccination.